(untitled) (The Journal of Sindhuli Multiple Campus, 2026)
The study investigates the factors influencing migration intention of the youths in Biratnagar, Nepal, with the focus on economic factors, educational and career perceptions, social and lifestyle aspirations and family and cultural influences. The study uses a quantitative research design where primary data were collected from 122 youths through structured questionnaires via google form and analyzes using SPSS software. Demographic analysis, descriptive statistics, reliability test, correlation analysis and multiple regression analysis were conducted where the findings revealed that economic factors and educational and career perceptions were the most significant factors of migration intention where social and lifestyle aspirations and family and cultural influences play a supportive role but were statistically insignificant role in regression model. More than half of the respondents were students, reflecting the views of the individuals who were in the early stage of their career and are actively considering migration as their pathway for financial security and career advancement. The data analysis is performed by the use of IBM 27 SPSS software, where the demographic analysis was performed and descriptive analysis is performed for all the statement. The reliability test was performed where the Cronbach’s alpha value is above the threshold. Positive correlation among the variables used in the study. The coefficient of individual predictors; economic factors (β = 0.362, p < 0.001) and educational and career perception (β = 0.334, p = 0.001) shows significantly positive influences on migration intentions in contrast to the social and lifestyle aspirations (β = 0.102, p = 0.315) and family and cultural influence (β = 0.036, p = 0.651).